Exploring the Transformative Impact of Language Teachers' Autoethnographies in a Teacher Education Course - Ekaterina Arshavskaya; Nefi Reyes de la Paz (Park University, 2023)
Benefits of teachers' autoethnographies are well-documented in current research. This study adds to the research literature by directly analyzing how the insights gained through writing autoethnographic essays may impact second language (L2) teachers' classrooms. To collect the data, the study incorporated autoethnographic essays into a graduate course for language teachers and asked the participating teachers to design lessons that reflected the insights they gained about themselves through this project. Adopting the transformative learning theory (Mezirow, 1978, 1997) that scaffolds teachers' self-reflection, this paper explores the transformative potential of teachers' autoethnographies through tracking qualitative changes in the teachers' narratives and practice across one academic semester. The results show that as a learning tool, autoethnographies can facilitate teachers' developing more empowering teaching identities and have a potential for enhancing their teaching practices. The paper adds empirical evidence and a new perspective in the investigation of teacher learning. It concludes with pedagogical and research implications for L2 teacher education.